2020
DOI: 10.1088/1757-899x/780/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

Brief Analysis of the Application and Limitation of BIM in Project Life Cycle Management

Abstract: BIM (building information model) with its advantages of information integration and excellent visualization effect has created considerable economic benefits and significantly improved work efficiency in construction practice. Although BIM is widely regarded as the future of China's construction industry, there are many obstacles to its application in China. This paper briefly analyzes the application status and main obstacles of BIM in China. At the end of the paper, the author provides some suggestions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They further note that complexity significantly increases when dealing with projects involving existing building data, such as original design drawings and the spatial relationships of existing infrastructures within service blocks to other surrounding spaces. Moreover, Li [12] underscores the substantial advantages of BIM technology in large and complex construction projects. In China, where BIM application primarily hinges on clients' specific needs and is limited to complex projects, BIM has become essential for constructors due to tight timelines, complex building shapes, and significant spatial relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further note that complexity significantly increases when dealing with projects involving existing building data, such as original design drawings and the spatial relationships of existing infrastructures within service blocks to other surrounding spaces. Moreover, Li [12] underscores the substantial advantages of BIM technology in large and complex construction projects. In China, where BIM application primarily hinges on clients' specific needs and is limited to complex projects, BIM has become essential for constructors due to tight timelines, complex building shapes, and significant spatial relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In China, where BIM application primarily hinges on clients' specific needs and is limited to complex projects, BIM has become essential for constructors due to tight timelines, complex building shapes, and significant spatial relationships. Li (2020) emphasizes that BIM is predominantly employed in complex building design to enhance design efficiency and conduct conflict checks, thereby reducing errors in drawings. However, Singh et al [11] caution against technological and implementation issues identified in case studies, which could pose significant obstacles to the widespread adoption of BIM servers in more complex projects.…”
Section: Introductionmentioning
confidence: 99%
“…Construction digitalization is gradually developing into full-scale digital transformation of the construction industry. In addition to known BIM technologies 9 [5,6], which are widely used in design, several Congress participants presented cutting-edge digital ecosystems of the full cycle [7], allowing to encompass nearly all stages of the life cycle of an investment and construction project.…”
mentioning
confidence: 99%